Franchise business development model: Theoretical considerations - Kavaliauskė, Monika; Vaiginienė, Erika (Business: Theory and Practice, 2011)
Franchising is not a popular business development form in Lithuania. Only 0.02% of all Lithuanian companies use franchising for business development, while in most of the developed countries franchise is recognized as a convenient business expansion form. So, what factors determine such differences in the use of franchising? Analysis of related literature showed, that mainly researchers analyse some aspects of franchising, however there is no systematized analysis which covers all the main franchise development elements. Therefore, the aim of this article is to systematize franchise business development phases, main elements and factors, influencing this process and to propose a theoretical franchise system development model. Thus, theoretical considerations about the main phases and elements of franchise system development as well as advantages and disadvantages of the system are analysed in the article. These theoretical considerations are generalized in theoretical franchise system development model, which shows, that development of franchise business consists of particular steps, starting from favourable conditions for the system to emerge; intention and ability of franchisor to form franchise based on his business; the establishment and initial development of franchise system; and its further functioning. The article does not test the model and even does not discuss the operationalization of it. Operationalization of the model as well as empirical evidence is presented by the authors in the forthcoming articles.